IDENTIFIKASI STRUKTUR BATUAN BAWAH PERMUKAAN MENGGUNAKAN METODE SEISMIK REFRAKSI DI KAMPUNG BARU BANJARBARU - Triningsih, Sumaos; Sota, Ibrahim; Wahyono, Sri Cahyo (Lambung Mangkurat University Press, 2013)
ABSTRACT: It has been researched graving hole of ex-coal mining using refractionseismic method in Kampung Baru Banjarbaru. The hole is filled by water as acidpuddle, where it is worried to flow through to soil layer by following the plot of rocklayerâs slope. Identification of subsurface structure of the area is in order to know thedirection of the waterâs flow. Seismograph PASI 24 Channel has been used to collectdata. The data has been processed using intercept time method. Interpretation resultsshow the subsurface in residential area has 3 layers. First layer is decayed layer withwave velocity (295-413 m/s) and thickness (2.8-5.57) m. Second layer with wavevelocity (787.4-919) m/s and thickness (10-11.66) m is interpreted as sand and gravel.Whereas, third layer with wave velocity (1282-2020) m/s and area boundary between h2dan h3 about (13.42-16.01) m is interpreted as clay (waterproof layer).Keywords: Seismic refraction, Intercept time method, Banjarbaru